Prognostic Value of Twist-1, E-cadherin and EZH2 in Prostate Cancer: An Immunohistochemical Study - Aziza E. ABDELRAHMAN; Shimaa A. ARAFA; Ragab A. AHMED (Federation of Turkish Pathology Societies, 2017)
Objective: There is an urgent need to identify molecular biomarkers rather than clinical markers to distinguish aggressive prostate cancer from the indolent majority for proper treatment and accurate prediction of prognosis. We aimed to investigate the immunohistochemical expression of epithelial-mesenchymal transition (EMT)-related molecules (Twist-1 and E-cadherin) and the stem cell marker EZH2 in prostate cancer and to assess their ability to identify the high-risk patients, in a trial to explore their prognostic implications. Material and Method: Immunohistochemical expression of Twist-1, E-cadherin and EZH2 in 50 specimens of prostate cancer and 20 cases of benign prostatic hyperplasia were studied. The relationship between their expression and the clinicopathological variables, biochemical recurrence, and biochemical progression-free survival were investigated. Results: Our results revealed that high Twist-1, as well as high EZH2 expression, was strongly associated with higher pre-treatment PSA level, Gleason score ≥7, advanced tumor stage, lymph node involvement, distant metastasis and biochemical progression. Aberrant E-cadherin expression was significantly associated with higher pre-treatment PSA level, Gleason score ≥7, advanced tumor stage, lymph node involvement, and distant metastasis. A significant positive correlation between Twist-1 and EZH2 expression was found (p<0.001), while E-cadherin expression showed a negative correlation with both markers (p<0.001). A significant association was found between high Twist-1, high EZH2& aberrant E-cadherin expression, and shorter biochemical progression-free survival. Conclusion: The high Twist-1 expression, aberrant E-cadherin and high EZH2 expression in primary prostate cancer are considered as adverse prognostic markers of an aggressive tumor with high metastatic potential. Assessment of their expression level would contribute to the accurate prediction of biochemical progression.